New biotechnological microencapsulating methodology utilizing individualized gradient-screened jet laminar flow techniques for pancreatic ß-cell delivery: bile acids support cell energy-generating mechanisms - Mooranian, A.; Negrulj, R.; Takechi, R.; Jamieson, E.; Morahan, G.; Al-Salami, Hani (American Chemical Society, 2017)
In previous studies, we developed a new technique (ionic gelation vibrational jet flow; IGVJF) in order to encapsulate pancreatic β-cells, for insulin in vivo delivery, and diabetes treatment. The fabricated microcapsules showed good morphology but limited cell functions. Thus, this study aimed to optimize the IGVJF technique, by utilizing integrated electrode tension, coupled with high internal vibration, jet-flow polymer stream rate, ionic bath-gelation concentrations, and gelation time stay. The study also utilized double inner/outer nozzle segmented-ingredient flow of microencapsulating dispersion, in order to form β-cell microcapsules. Furthermore, a microcapsule-stabilizing bile acid was added, and microcapsule’s stability and cell functions measured. Buchi-based built-in system utilizing IGVJF technology was screened to produce best microcapsule-containing β-cells with or without a stabilizing-enhancing bile acid. Formed microcapsules were examined, for physical characteristics, and encapsulated cells were examined for survival, insulin release, and inflammatory profiles. Optimized microencapsulating parameters, using IGJVF, were: 1000 V voltage, 2500 Hz frequency, 1 mL/min flow rate, 3% w/v ionic-bath gelation concentration, and 20 min gelation time. Microcapsules showed good morphology and stability, and the encapsulated cells showed good survival, and insulin secretion, which was optimized by the bile acid. Deployed IGVJF-based microencapsulating parameters utilizing stability-enhancing bile acid produced best microcapsules with best pancreatic β-cells functions and survival rate, which, suggests potential application in cell transplantation.